2015
DOI: 10.3109/09638237.2015.1057320
|View full text |Cite
|
Sign up to set email alerts
|

A survey of psychiatrists’ attitudes towards the physical examination

Abstract: Background: Studies have shown that most psychiatric patients do not receive a thorough physical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…This national survey, which obtained views from psychiatrists in all the main sub-specialities, clarifies considerably the factors contributing to the standard of PEs performed on psychiatric patients. The results show, as did an earlier regional survey, that most psychiatrists view the PE as important, think that skills in this domain should be part of their core competencies which should be maintained throughout their career, and do not believe that it has a negative effect on the patient (Murray, et al, 2015). The survey responses also indicate that most psychiatrists rate their PE competencies as good or mediocre and that they are in favour of using structured forms to document the PE findings, a practice which has been shown to increase the amount of information recorded (Murray & Baillon, 2013).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This national survey, which obtained views from psychiatrists in all the main sub-specialities, clarifies considerably the factors contributing to the standard of PEs performed on psychiatric patients. The results show, as did an earlier regional survey, that most psychiatrists view the PE as important, think that skills in this domain should be part of their core competencies which should be maintained throughout their career, and do not believe that it has a negative effect on the patient (Murray, et al, 2015). The survey responses also indicate that most psychiatrists rate their PE competencies as good or mediocre and that they are in favour of using structured forms to document the PE findings, a practice which has been shown to increase the amount of information recorded (Murray & Baillon, 2013).…”
Section: Discussionsupporting
confidence: 63%
“…The questionnaire obtained basic information about the respondent and then included questions with categorical and Likert scale responses. Questions were based on a range of issues included in a previous survey (Murray, et al, 2015) and included items on physical examinations in their current (or if retired, most recent) job and on their views about physical examinations in psychiatry. Respondents were asked about their physical examination skills and supervision of junior trainees in this domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular relevance is a survey completed by Murray et al 14 which examined factors contributing to underperformance of physical examinations in psychiatric patients. The study's authors concluded that completing a physical examination should be part of psychiatrists' core competencies, but senior psychiatrists reported their skills had diminished.…”
Section: Specific Systems Examination and Managementmentioning
confidence: 99%
“…Other barriers included time difficulties, lack of equipment and difficulties with uncooperative and agitated patients limiting the ability to complete a detailed examination. The study also made reference to trainees having inadequate supervision, which may further compound the problem 14,15 Another barrier to psychiatrists taking the lead on physical health care may relate to availability of resources. Alam et al 16 explored what resources were available for consultant psychiatrists working in North West England, looking at ECG monitoring of patients on high-dose antipsychotic treatment, as well as availability of resources for measuring blood pressure.…”
Section: Specific Systems Examination and Managementmentioning
confidence: 99%